Pengaturan Mengenai Akibat Hukum Bagi Pelaku Usaha Yang Telah Mendaur Ulang Limbah Sampah Makanan - Mario Kusdianto; Rory Jeff Akyuwen; Marselo Valentino Geovani Pariela (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Court decisions that are enforced are relatively soft, they do not cause a deterrent effect for perpetrators of violations. Especially in the food sector, business people are sentenced to 15 (fifteen) days to 8 (eight) months in prison, a probationary period of one year and 6 (six) months, and pay fines ranging from Rp. 50,000 to Rp. 400,000, 00 subsidy 15 (fifteen) days.Purposes of the Research: This paper aims to find out what legal sanctions are imposed on actors in businesses that recycle food waste.Methods of the Research: The method used is a normative juridical research method using a case approach, a statutory approach and a conceptual approach.Results of the Research: The results obtained from the study show that the sanctions regulations imposed on entrepreneurs who recycle food waste are: in Law Number 8 of 1999 concerning Consumer Protection (UUPK) (1) Administrative sanctions, the Consumer Dispute Settlement Agency (BPSK) provides sanctions This is for the duties and/or powers conferred by law. This penalty is stated in Article 60. According to the provisions of Article 60 (1) and (2), the UUPK indicates that the administrative penalty that can be abandoned by BPSK is in the form of determining compensation up to a maximum of Rp. 200,000,000.00 (two hundred million rupiah). (2) Principal Criminal Sanctions, These sanctions are sanctions that can be imposed on entrepreneurs from the courts due to claims for violations. This sanction is stated in Article 62 of the UUPK, this sanction can be applied in two forms, namely, fines or imprisonment. (3) Additional Criminal Sanctions, these sanctions are regulated in Article 63 of the UUPK. The forms of additional criminal sanctions that can be imposed are in the form of confiscation of certain goods, announcement of judge's decisions, payment of compensation, orders to stop certain activities that cause consumer losses, and revocation of business licenses.